Social representations and social marketing: Effectiveness of awareness campaigns on the representation of public policies?. Issue 2 (28th November 2018) - Bordarie, Jimmy
Abstract : The research fits into the theory of the central core within the social representations theory. The approach argues the existence of two components: the core and the periphery. Each one has its own characteristics and a role to play. Within this framework, transformation of social representations can be the consequence of practices modification. However, in this study, we are interested in the effect of communication. We focus on the social representation of the public policy of the 30 kmh speed limit developed in Europe since the 1990's. And we test the impact of two awareness campaigns: the first one aims at reinforcing one aspect of the central core of the representation, the second one aims at contradicting one aspect of the core. Three groups of participants answer a questionnaire of representation related to the 30 kmh speed limit: two experimental groups (each one receiving a campaign) and one control group. Results confirm the relevance of using communication and social marketing methods in order to transform social representations. According to the type information, results are different. Discussion highlights the interest of using social representations in order to build social marketing campaigns.